2014
DOI: 10.4048/jbc.2014.17.4.332
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid 1 Expression and Functionality in MCF-7 Cells: A Preliminary Investigation

Abstract: PurposeTransient receptor potential vanilloid 1 (TRPV1) is a nonselective cation channel belonging to the transient receptor potential family, and it is expressed in different neoplastic tissues. Its activation is associated with regulation of cancer growth and progression. The aim of this research was to study the expression and pharmacological characteristics of TRPV1 in cells derived from human breast cancer MCF-7 cells.MethodsTRPV1 presence was assessed by binding studies and Western blotting. Receptor bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…In our experiments, a significant reduction in cell proliferation after capsaicin stimulation was observed, diminished by the coapplication of capsazepin. This finding was in accordance with the results of Vercelli et al,43 who demonstrated a significant decrease in the cell growth rate of MCF-7 breast cancer cells upon capsaicin stimulation. Interestingly, Zheng et al44 furthermore showed that capsaicin was capable of enhancing the antineoplastic effects of pirarubicin, which is an analog of the antibiotic doxorubicin 45.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our experiments, a significant reduction in cell proliferation after capsaicin stimulation was observed, diminished by the coapplication of capsazepin. This finding was in accordance with the results of Vercelli et al,43 who demonstrated a significant decrease in the cell growth rate of MCF-7 breast cancer cells upon capsaicin stimulation. Interestingly, Zheng et al44 furthermore showed that capsaicin was capable of enhancing the antineoplastic effects of pirarubicin, which is an analog of the antibiotic doxorubicin 45.…”
Section: Discussionsupporting
confidence: 93%
“…After we proved the existence and functionality of TRPV1, we conducted proliferation and migration analyses to investigate the long-term effects of capsaicin on SUM149PT cells. In a study by Sanchez et al,43 the role of TRPV1 in prostate cancer cell proliferation was analyzed. In our experiments, a significant reduction in cell proliferation after capsaicin stimulation was observed, diminished by the coapplication of capsazepin.…”
Section: Discussionmentioning
confidence: 99%
“…Virtually all pharmacological and molecular methods used to examine the function of these channels resulted in a decrease of cell viability. These methods included molecular up-or downregulation of the channels and activation or inhibition of channels with natural exogenous agonists or synthetic antagonists [16,17]. The activation of these channels leads to an increase in c cyt in breast and prostate cell lines, but the previously published studies presented only the average of evoked Ca 2+ cytoplasmic signals within the entire cell populations [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These methods included molecular up-or downregulation of the channels and activation or inhibition of channels with natural exogenous agonists or synthetic antagonists [16,17]. The activation of these channels leads to an increase in c cyt in breast and prostate cell lines, but the previously published studies presented only the average of evoked Ca 2+ cytoplasmic signals within the entire cell populations [17][18][19]. This method blurs the spatiotemporal character of individual intracellular Ca 2+ signals, which is essential to understand how TRPV1-mediated stimuli influence the cell behavior at the single cell level.…”
Section: Introductionmentioning
confidence: 99%
“…These results found a confirmation in other studies that demonstrated that capsaicin could inhibit human cancer hormone-resistant cells and can provide chemopreventive effects [58] . Moreover, other studies demonstrated that capsaicin can mediate cell death of T24 (human bladder cancer), A172 (human glioma) [59; 60] , and MCF-7 [61] cell lines, nevertheless the use of TRPV1 ligands in cancer treatment should always be careful, as explained previously.…”
Section: Trpv1 In Comparative Medicinementioning
confidence: 99%